Employability or self-respect? Justifying the use of volunteering to address unemployment. (1st July 2019) - Penny, Richard; Finnegan, Anjelica
Abstract : British governments continue to support volunteering initiatives as a means to address unemployment. In this article we describe how the primary justification for this support has been (and remains) that it provides 'access to work' for unemployed individuals. We then highlight evidence that volunteering performs poorly in this regard, with weak or inconsistent effects in terms of employability. As such, we argue that policy makers and voluntary organisations require alternative justifications for further cooperation in this area. We suggest and develop an alternative justificatory frame, built around volunteering offering long-term unemployed people 'access to self-respect'. We argue that this justification has both strong normative appeal and a much more secure evidence base for policy. We conclude that this justificatory frame offers an opportunity for policy makers and voluntary organisations to refocus their cooperation in addressing unemployment.